2006
DOI: 10.1103/physrevlett.97.026801
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Direct Tunneling to Field Emission in Metal-Molecule-Metal Junctions

Abstract: Current-voltage measurements of metal-molecule-metal junctions formed from pi-conjugated thiols exhibit an inflection point on a plot of ln(I/V(2)) vs 1/V, consistent with a change in transport mechanism from direct tunneling to field emission. The transition voltage was found to scale linearly with the offset in energy between the Au Fermi level and the highest occupied molecular orbital as determined by ultraviolet photoelectron spectroscopy. Asymmetric voltage drops at the two metal-molecule interfaces caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
725
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 572 publications
(784 citation statements)
references
References 27 publications
54
725
2
3
Order By: Relevance
“…[34,161,162] Experimentally, it is fairly simple to identify this transition bias (V T ) and indeed, in the study cited, [34,161,162] V T correlated well with the expected barrier height, the difference of the molecular level (highest occupied molecular orbital, HOMO) and the electrode Fermi level as deduced independently by UPS (see, however, Section 5.2). [52,161,162] This approach assumes a roughly linear J-V relation for tunneling transport [161] (i.e., positive ln(J/V 2 ) vs. 1/V slope), and in that case V T indeed indicates a change in transport mechanism to field-emission. However, as the barrier width/height ratio (which we called ''shape factor'' [149,159] ) increases, the tunneling J-V becomes more non-linear.…”
Section: Extracting Insulator Parameters From Current-density-voltagementioning
confidence: 52%
See 1 more Smart Citation
“…[34,161,162] Experimentally, it is fairly simple to identify this transition bias (V T ) and indeed, in the study cited, [34,161,162] V T correlated well with the expected barrier height, the difference of the molecular level (highest occupied molecular orbital, HOMO) and the electrode Fermi level as deduced independently by UPS (see, however, Section 5.2). [52,161,162] This approach assumes a roughly linear J-V relation for tunneling transport [161] (i.e., positive ln(J/V 2 ) vs. 1/V slope), and in that case V T indeed indicates a change in transport mechanism to field-emission. However, as the barrier width/height ratio (which we called ''shape factor'' [149,159] ) increases, the tunneling J-V becomes more non-linear.…”
Section: Extracting Insulator Parameters From Current-density-voltagementioning
confidence: 52%
“…[149,159,161,162] One approach postulates that if the applied bias is larger than the barrier height, the transport mechanism changes from direct tunneling to field-emission. [34,161,162] Experimentally, it is fairly simple to identify this transition bias (V T ) and indeed, in the study cited, [34,161,162] V T correlated well with the expected barrier height, the difference of the molecular level (highest occupied molecular orbital, HOMO) and the electrode Fermi level as deduced independently by UPS (see, however, Section 5.2). [52,161,162] This approach assumes a roughly linear J-V relation for tunneling transport [161] (i.e., positive ln(J/V 2 ) vs. 1/V slope), and in that case V T indeed indicates a change in transport mechanism to field-emission.…”
Section: Extracting Insulator Parameters From Current-density-voltagementioning
confidence: 99%
“…The difference in β for aliphatic and aromatic carboxylates is in agreement with predictions based on molecular orbital (MO) theory. 2,4,8 Aromatic molecules are characterized by smaller energy gaps (∼3−5 eV) between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) than those of aliphatic molecules (∼7 eV) of similar length. 2,48 Furthermore, the HOMO of aromatic molecules aligns more favorably with the Fermi level of electrodes than does that of aliphatic molecules; this alignment, in a SAM-based tunneling junction, facilitates charge transport by lowering the effective height of the tunneling barrier.…”
Section: ■ Backgroundmentioning
confidence: 99%
“…Using a potential barrier model that explicitly assumes constant contributions to rates of tunneling from the interfaces between the SAMs and the electrodes, we found that (CH 2 ) n and (C 6 H 4 ) m segments contribute independently but differently to the shape of the tunneling barrier and that the values of β for (CH 2 ) n and (C 6 H 4 ) m are independent of the order in which they are assembled. 4 We expect this conclusion to hold only when the molecular units (R) being considered are isolated electronically from strong interactions with the electrodes.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…It can be compared to a tunneling barrier, which charge carriers have to overcome to generate a current. Ultraviolet photoelectron spectroscopy (UPS) 1 , thermopower [2][3][4] , and transition voltage spectroscopy (TVS) [5][6][7][8][9][10] represent current methods to estimate the relative alignment of the dominant molecular orbital from experimental data.…”
Section: Introductionmentioning
confidence: 99%